Development, Optimization and Evaluation of Polyherbal Gel Comprising of Azadirachta Indica, Calendula Officenalis, Turmeric and Aloe-vera for Treatment of Wound - Yograj Mahajan; Vishal Gupta (Recent Trends in Cosmetics, 2025)
Azadirachta indica, Calendula officinalis, Turmeric (Curcuma longa), and Aloe-vera are known to possess numerous medicinal properties. These herbs have been traditionally used across various cultures for the treatment of a wide range of ailments due to their potent therapeutic effects. Individually, they have demonstrated efficacy in addressing conditions such as acne, diabetes, wound healing, gastric ulcers, first-degree burns, psoriasis, arthritis, and pneumonia. Additionally, they are known for their antimicrobial, anti-inflammatory, antifungal, antibacterial, and antimalarial properties, making them valuable components in traditional and modern herbal medicine. In the present study, a polyherbal gel formulation comprising Azadirachta indica, Calendula officinalis, Turmeric, and Aloe-vera was prepared with the objective of evaluating its wound-healing efficacy. Ten different formulations were developed and tested for drug release properties and drug content. Among these, formulations F-2, F-6, and F-9 demonstrated the highest percentage of drug release, showing approximately 95.98%, 91.3%, and 87.62% release respectively from the gel matrix. Furthermore, the drug content in these formulations was found to be notably high, with values of 96.86%, 97.82%, and 98.07% respectively. These findings indicate that the active constituents were well incorporated within the gel base. Further research on formulated gel shows its clinical effectiveness in the treatment of wound.
Keywords: Aloe-vera; Azadirachta indica; Burn wound; Calendula officenalis; Polyherbal gel; Wound; herbal formulation; hydroalcoholic; turmeric